Innovation Ecosystem: Understanding Sustainable Development Through Technology - Divya Nama; Ankit Kushwaha; Anurag Shukla; Ram Mohan (International Journal of Sustainability, 2025)
Over the past 15 years, the notion of “Innovation Ecosystem” has captured the attention of scholars and practitioners alike. The increasing interest underscores the growing acknowledgement of the pivotal role played by Innovation Ecosystems in driving societal and economic advancement. This research work aims to explore innovation ecosystems, focusing on how they work, the challenges they face and their potential for driving sustainable progress. Overall, the goal is to improve our understanding of the innovation ecosystem, helping to create a stronger and more effective system for innovation and growth. We identified five main areas of research on innovation ecosystems: technology, platforms, regional development, policy and governance, and the conceptualization and definition of innovation ecosystems. In conclusion, this research sheds light on the diverse landscape of innovation ecosystem literature, uncovering five key areas of focus. By employing rigorous methodology, we have synthesized the core and latest knowledge in this field, offering valuable insights for both scholars and practitioners.
Keywords: Societal and economic; ecosystem; literature; methodology; sustainable progress